The Impact of Organizational Change on Change Management in ICT sector in the Republic of Croatia (International Journal of Applied Research in Management and Economics, 2021)
In recent years, the information and communication technology (ICT) sector has recorded rapid growth and development and is the driving force of the Croatian economy. At the same time, this sector is characterized by fast and dynamic changes which in the demanding business environment requires an immediate and adequate response, so the question of how organizational changes affect change management in ICT sector in the Republic of Croatia arises. To answer this question, empirical research was conducted. The research sample is structured according to data collected from 103 experts in Croatian ICT sector. It offers sufficient elements to establish a quality methodological framework to monitor the impact of organizational change on change management in this sector. This empirical research offered evidence on the possibility of using the ADKAR model of change management in analysis of need for change, implementation, and monitoring of the course of change in ICT organizations. The research results point to the conclusion that organizational change presented through ADKAR model has an impact on change management and is of key importance for ICT organizations. This paper contributes to a better understanding of organizational change and its significance for change management in Croatian ICT organizations.